The PIFA-initiated oxidative cyclization of 2-(3-butenyl)quinazolin-4(3H)-ones – an efficient approach to 1-(hydroxymethyl)-2,3-dihydropyrrolo[1,2-a]quinazolin-5(1H)-ones - Vaskevych, Alla I.; Savinchuk, Nataliia O.; Vaskevych, Ruslan I.; Rusanov, Eduard B.; Grygorenko, Oleksandr O.; Vovk, Mykhailo V. (Beilstein Journal of Organic Chemistry, 2021)
A regioselective method for the synthesis of 1-(hydroxymethyl)-2,3-dihydropyrrolo[1,2-a]quinazolin-5(1H)-ones – close structural analogs of naturally occurring vasicinone alkaloids – is described. The procedure is based on PIFA-initiated oxidative 5-exo-trig cyclization of 2-(3-butenyl)quinazolin-4(3Н)-ones, in turn prepared by thermal cyclocondensation of the corresponding 2-(pent-4-enamido)benzamides. The products obtained have a good natural product likeness (NPL) score and therefore can be useful for the design of natural product-like compound libraries.
Keywords: [bis(trifluoroacetoxy)iodo]benzene PIFA; nitrogen heterocycles; oxidative cyclization; pyrrolo[1,2-a]quinazolines

(untitled) - Ertl, P.; Roggo, S.; Schuffenhauer, A. (J. Chem. Inf. Model., 2008)

(untitled) - Kumar, K.; Waldmann, H. (Isr. J. Chem., 2019)

(untitled) - Grygorenko, O. O.; Volochnyuk, D. M.; Ryabukhin, S. V.; Judd, D. B. (Chem. – Eur. J., 2020)

(untitled) - Sorokina, M.; Steinbeck, C. (J. Cheminf., 2019)

(untitled) - Dumitrascu, F.; Georgescu, F.; Georgescu, E.; Caira, M. R. (Adv. Heterocycl. Chem., 2019)

(untitled) - Mhaske, S. B.; Argade, N. P. (Tetrahedron, 2006)

(untitled) - Shang, X.-F.; Morris-Natschke, S. L.; Liu, Y.-Q.; Guo, X.; Xu, X.-S.; Goto, M.; Li, J.-C.; Yang, G.-Z.; Lee, K.-H. (Med. Res. Rev., 2018)

(untitled) - Shang, X.-F.; Morris-Natschke, S. L.; Yang, G.-Z.; Liu, Y.-Q.; Guo, X.; Xu, X.-S.; Goto, M.; Li, J.-C.; Zhang, J.-Y.; Lee, K.-H. (Med. Res. Rev., 2018)

(untitled) - Stavytskyi, V.; Antypenko, O.; Nosulenko, I.; Berest, G.; Voskoboinik, O.; Kovalenko, S. (Anti-Inflammatory Anti-Allergy Agents Med. Chem., 2021)

(untitled) - Kazemi, S. S.; Keivanloo, A.; Nasr-Isfahani, H.; Bamoniri, A. (RSC Adv., 2016)

U.S. Patent - Ostersehlt, B.; Schlecker, R.; Rendenbach, B.; von Philipsborn, G.; Franke, A. (Tetracyclic quinazoline derivatives, effective as antiarrythmic agents, 1993)

(untitled) - Dumitrascu, F.; Popa, M. M. (ARKIVOC, 2014)

(untitled) - Mori, K.; Ohshima, Y.; Ehara, K.; Akiyama, T. (Chem. Lett., 2009)

(untitled) - Sun, X.; Hu, Y.; Nie, S.-z.; Yan, Y.-y.; Zhang, X.-j.; Yan, M. (Adv. Synth. Catal., 2013)

(untitled) - Patil, N. T.; Kavthe, R. D.; Raut, V. S.; Shinde, V. S.; Sridhar, B. (J. Org. Chem., 2010)

(untitled) - Feng, E.; Zhou, Y.; Zhang, D.; Zhang, L.; Sun, H.; Jiang, H.; Liu, H. (J. Org. Chem., 2010)

(untitled) - Patil, N. T.; Lakshmi, P. G. V. V.; Sridhar, B.; Patra, S.; Bhadra, M. P.; Patra, C. R. (Eur. J. Org. Chem., 2012)

(untitled) - Jia, X.; Li, P.; Liu, X.; Lin, J.; Chu, Y.; Yu, J.; Wang, J.; Liu, H.; Zhao, F. (Molecules, 2019)

(untitled) - Naidu, S.; Reddy, S. R. (ChemistrySelect, 2017)

(untitled) - Zhou, J.-X.; Lu, L.; Li, T.-J.; Yao, C.-S.; Wang, X.-S. (J. Heterocycl. Chem., 2014)

(untitled) - Lu, L.; Yang, K.; Zhang, M.-M.; Wang, X.-S. (J. Heterocycl. Chem., 2014)

(untitled) - Zhang, W.-T.; Qiang, W.-W.; Yao, C.-S.; Wang, X.-S. (Tetrahedron, 2016)

(untitled) - Liu, J.-Q.; Zhang, W.-T.; Wang, X.-S. (J. Heterocycl. Chem., 2018)

(untitled) - Iminov, R. T.; Tverdokhlebov, A. V.; Tolmachev, A. A.; Volovenko, Y. M.; Shishkina, S. V.; Shishkin, O. V. (Tetrahedron, 2009)

(untitled) - Zicāne, D.; Tetere, Z.; Rāviņa, I.; Turks, M. (Chem. Heterocycl. Compd., 2013)

(untitled) - Sutherell, C. L.; Tallant, C.; Monteiro, O. P.; Yapp, C.; Fuchs, J. E.; Fedorov, O.; Siejka, P.; Müller, S.; Knapp, S.; Brenton, J. D.; Brennan, P. E.; Ley, S. V. (J. Med. Chem., 2016)

(untitled) - Sutherell, C. L.; Ley, S. V. (Synthesis, 2017)

(untitled) - Wang, M.; Dou, G.; Shi, D. (J. Comb. Chem., 2010)

(untitled) - Zhao, X.; Shi, D.-Q. (J. Heterocycl. Chem., 2011)

(untitled) - Bunce, R. A.; Nammalwar, B. (J. Heterocycl. Chem., 2011)

(untitled) - Singh, P.; Kaur, N.; Banerjee, P. (J. Org. Chem., 2020)

(untitled) - Boomhoff, M.; Ukis, R.; Schneider, C. (J. Org. Chem., 2015)

(untitled) - Volovenko, Y. M.; Resnyanskaya, E. V. (Mendeleev Commun., 2002)

(untitled) - Mhaske, S. B.; Argade, N. P. (J. Org. Chem., 2001)

(untitled) - Fang, J.; Zhou, J. (Org. Biomol. Chem., 2012)

(untitled) - Wang, H.; Jiao, S.; Chen, K.; Zhang, X.; Zhao, L.; Liu, D.; Zhou, Y.; Liu, H. (Beilstein J. Org. Chem., 2015)

(untitled) - Stang, P. J.; Zhdankin, V. V. (Chem. Rev., 1996)

(untitled) - Zhdankin, V. V.; Stang, P. J. (Chem. Rev., 2002)

(untitled) - Yoshimura, A.; Zhdankin, V. V. (Chem. Rev., 2016)

(untitled) - Yang, Y. O.; Wang, X.; Xiao, J.; Li, Y.; Sun, F.; Du, Y. (Curr. Org. Chem., 2021)

(untitled) - Tellitu, I.; Domínguez, E. (Trends Heterocycl. Chem., 2011)

(untitled) - Tellitu, I.; Urrejola, A.; Serna, S.; Moreno, I.; Herrero, M. T.; Domínguez, E.; SanMartin, R.; Correa, A. (Eur. J. Org. Chem., 2007)

(untitled) - Saito, A.; Anzai, T.; Matsumoto, A.; Hanzawa, Y. (Tetrahedron Lett., 2011)

(untitled) - Wardrop, D. J.; Bowen, E. G.; Forslund, R. E.; Sussman, A. D.; Weerasekera, S. L. (J. Am. Chem. Soc., 2010)

(untitled) - Bowen, E. G.; Wardrop, D. J. (Org. Lett., 2010)

(untitled) - Wardrop, D. J.; Bowen, E. G. (Org. Lett., 2011)

(untitled) - Serna, S.; Tellitu, I.; Domı́nguez, E.; Moreno, I.; SanMartı́n, R. (Tetrahedron Lett., 2003)

(untitled) - Correa, A.; Tellitu, I.; Domínguez, E.; Moreno, I.; SanMartin, R. (J. Org. Chem., 2005)

(untitled) - Wardrop, D. J.; Basak, A. (Org. Lett., 2001)

(untitled) - Wardrop, D. J.; Zhang, W. (Org. Lett., 2001)

(untitled) - Wardrop, D. J.; Burge, M. S.; Zhang, W.; Ortı́z, J. A. (Tetrahedron Lett., 2003)

(untitled) - Wardrop, D. J.; Zhang, W.; Landrie, C. L. (Tetrahedron Lett., 2004)

(untitled) - Bhattacharjee, A.; Gerasimov, M. V.; DeJong, S.; Wardrop, D. J. (Org. Lett., 2017)

(untitled) - He, L.; Li, H.; Chen, J.; Wu, X.-F. (RSC Adv., 2014)

(untitled) - Ramana, D. V.; Sundaram, N.; Yuvaraj, T. E.; Babu, B. G. (Indian J. Chem., Sect. B: Org. Chem. Incl. Med. Chem., 1999)

(untitled) - Fiorito, S.; Taddeo, V. A.; Epifano, F.; Genovese, S. (ARKIVOC, 2016)

(untitled) - Das, M.; Rodríguez, A.; Lo, P. K. T.; Moran, W. J. (Adv. Synth. Catal., 2021)

(untitled) - Butt, S. E.; Das, M.; Sotiropoulos, J.-M.; Moran, W. J. (J. Org. Chem., 2019)

(untitled) - Hamasharif, M. S.; Smith, O. E. P.; Curran, C. J.; Hemming, K. (ACS Omega, 2017)